PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING (GUIDED INQUIRY) TERHADAP KETERAMPILAN PROSES SAINS - ANDRIONO MANALU (JURNAL ILMIAH SIMANTEK, 2020)
The purpose of this study was to determine the effect of guided inquiry learning models on students' science process skills.The approach taken in this study is a qualitative descriptive approach, meaning that the data collected is the result ofobservations and written test results that are processed descriptively in writing to find out the high level thinking skills of classX SMA Negeri 2 Pematangsiantar T.P 2019/2020 in guided inquiry learning. The science process skills instrument used tomeasure students' science process skills consists of science process skills tests. Science process skills tests are given in theform of essay questions from each aspect of science process skills, including: 1) observing, observing questions, 3)formulating hypotheses, 4) predicting, 5) finding patterns and relationships, 6) communicating effective, 7) design anexperiment 8) carry out an experiment, and 9) measure and count. This test is given twice, namely during the pre-test andpost-test. Based on the calculation of the N-gain value of the experimental class obtained an increase of 0.748 in the highcategory, in the conventional class an increase of 0.293 was obtained in the low category. Based on testing the hypothesis ofscience process skills with a tcount of 42.379 and a significance of 0.00 (ttable = 1.67, α = 0.05). These results indicate thattcount> ttable and the significance value is smaller than 0.05. Based on these results it is concluded that the guided inquirylearning model has a significant effect on students' science process skills.